RUJUK DI NEGARA-NEGARA MUSLIM; YORDANIA, YAMAN, LIBYA DAN SOMALIA - Puji Kurniawan (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2021)
Marriage has a very noble purpose, namely to form a sakinah, mawaddah, wa rahmah household. However, in living a married life, it is not always smooth. There are also crucial moments that can endanger the household that has been fostered. For those who are strong, then they can maintain the integrity of the household, while for those who are not strong with various challenging problems, divorce is the last solution. then this paper will explain about the various forms of divorce procedures in various Muslim countries in the world.